TINDAK TUTUR DALAM TALKSHOW HITAM PUTIH DI TRANS 7 - Sri Budi Astuti; Ira Eko Retnosari (EDU-KATA, 2018)
This study aimed to describe the illocutionary speech acts include: assertive, directive, commissive, expressive and declarative in a Hitam Putih talk show in Trans7. In this study, the data in the form of illocutionary speech acts that include: assertive, directive, commissive, expressive and declarative. Meanwhile, the source of the data acquired from the television talk show on Trans7. The data collection method is used refer to the recording technique and technique noted.Analysis of the data in this study used a qualitative descriptive method. In this method, use the following steps: (1) the selection of data, (2) an understanding of data, (3) classification of data, and (4) an explanation and interpretation. Based on the results of data analysis, it can be concluded that expressive speech acts was found includes (1) thanked, (2) congratulate, (3) forgiving, (4) blasted, (5) praise, and (6) insulting. Assertive speech acts, among others, (1) state information, (2) expression, (3) expressed sympathy, and (4) boasting. Commissive speech acts include (1) a promising and (2) offer. Directive speech acts include (1) requesting information and (2) rule.